2009
DOI: 10.1051/0004-6361/200811392
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen in dense interstellar gas

Abstract: Context. Oxygen is the third most abundant element in the universe, but its chemistry in the interstellar medium is still not understood well. Aims. To critically examine the entire oxygen budget, we initially attempt to estimate the abundance of atomic oxygen, O, in the only region where molecular oxygen, O 2 , has been detected to date. Methods. We analysed ISOCAM-CVF spectral image data toward ρ Oph A to derive the temperatures and column densities of H 2 at the locations of ISO-LWS observations of two [O I… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…A value of about 450 was found by Liseau et al (1995) for L 1688 using CS maps and 60 µm IRAS data. A high g2d would also be consistent with the low oxygen abundance in ρ Oph A found by Liseau & Justtanont (2009). Figure 11 of Brinchmann et al (2013), which is based on a large number of galaxies, supports this view on larger, extragalactic scales.…”
Section: Introductionsupporting
confidence: 76%
“…A value of about 450 was found by Liseau et al (1995) for L 1688 using CS maps and 60 µm IRAS data. A high g2d would also be consistent with the low oxygen abundance in ρ Oph A found by Liseau & Justtanont (2009). Figure 11 of Brinchmann et al (2013), which is based on a large number of galaxies, supports this view on larger, extragalactic scales.…”
Section: Introductionsupporting
confidence: 76%
“…Observations of the fine structure components of O I at 63 µm ( 3 P 1 -3 P 2 ) and 145 µm ( 3 P 0 -3 P 1 ) of the inverted ground state with the ISO-LWS (Long Wavelength Spectrometer, Clegg et al 1996) towards the VLA 1623 outflow have been presented earlier by Liseau & Justtanont (2009). On OD 1202, the Photodetector Array Camera and Spectrometer (PACS, Poglitsch et al 2010) was used to map the fine structure line emission north of the outflow (see Fig.…”
Section: O Imentioning
confidence: 89%
“…To estimate the absolute accuracy of the fluxes we compared data from one map position with those that we previously obtained with the ISO-LWS (e.g. Liseau & Justtanont 2009). However, we refer here to re-reduced data using the final version of the pipeline (OLP 10).…”
Section: O Imentioning
confidence: 99%
“…Summarizing the main results of this analysis, Nisini et al (2015) find that while the density of colliders is rather well constrained (ranging between 10 4 − 10 5 cm −3 ), the nature of the colliders (atomic or molecular hydrogen) can affect the 63µm [O i] emissivity by a factor ranging between 2 and 5. In an order study, Liseau & Justtanont (2009) demonstrated that the emissivity of the 63 µm line can vary up to a factor of three for kinetic temperatures higher than 300 K, while in the same study they find that the excitation of the [O i] 63 µm line typically traces kinetic temperatures of ∼ 1000 K.…”
Section: Mass Momentum and Energymentioning
confidence: 94%